Anatomical and Chemical Analysis in Solidago chilensis var. chilensis (Asteraceae) - Hernandez, Marcelo P. (2013)
Solidago chilensis Meyen var. chilensis (Asteraceae) is a weed with an ample distribution in Argentina. The objective of this paper was to deepen the organs anatomy knowledge and to perform a preliminary chemical evaluation to detect constituents present in them. Root, rhizome, aerial stem, leaf and inflorescence structures were studied using conventional methods. Histochemical methods were used to identify plant constituents, inulin, lipophilic substances, and starch. Plant extracts of many species are used in biological control of pathogen microorganisms. Solidago chilensis var. chilensis can be seen as a potential source of extracts production to control pathogens.